Diet regulates liver autophagy differentially in murine acute Trypanosoma cruzi infection - Lizardo, Kezia (Parasitol Res, 2016)
Chagas disease is a tropical parasitic disease caused by the protozoan Trypanosoma cruzi, which affects about 10 million people in its endemic regions of Latin America. After the initial acute stage of infection, 60–80% of infected individuals remain asymptomatic for several years to a lifetime; however, the rest develop the debilitating symptomatic stage, which affects the nervous system, digestive system and heart. The challenges of Chagas disease have become global due to immigration. Despite well documented dietary changes accompanying immigration, as well as a transition to a western style diet in the Chagas endemic regions, the role of host metabolism in the pathogenesis of Chagas disease remains underexplored. We have previously used a mouse model to show that host diet is a key factor regulating cardiomyopathy in Chagas disease. In this study we investigated the effect of a high fat diet on liver morphology and physiology, lipid metabolism, immune signaling, energy homeostasis, and stress responses in the murine model of acute T. cruzi infection. Our results indicate that in T. cruzi infected mice diet differentially regulates several liver processes, including autophagy, a stress response mechanism, with corresponding implications for human Chagas disease patients.